Analgesic potential of transdermal nicotine patch in surgery: a systematic review and meta-analysis of randomised placebo-controlled trials - da Silva Barbirato, Davi; de Melo Vasconcelos, Amanda Freire; Dantas de Moraes, Sandra Lúcia; Pellizzer, Eduardo Piza [UNESP]; do Egito Vasconcelos, Belmiro Cavalcanti (Springer Nature, 2023)
Objectives: We aimed (1) to systematically review the efficacy of transdermal nicotine patches (NP) for postoperative analgesia, (2) to establish the current quality of evidence and assist clinical decision-making on the subject, and (3) to identify methodological limitations and the need for more well-designed studies. Materials and methods: We searched six electronic databases, protocol records, and other sources without date or language restriction until March 2022. To develop the search strategy, we formulated a clinical question by using the PICOD method. Eligibility criteria included randomised placebo-controlled trials on the analgesic potential of NP for surgical procedures. This systematic review followed the PRISMA 2020 statement, and we registered the protocol in PROSPERO (#CRD42020205956). Results: We included 10 randomised placebo-controlled trials (535 patients). The NP administered before induction of anaesthesia and at beginning of surgery reduced the pain immediately after surgery (−0.38; 95% confidence interval [CI]: −0.73 to −0.02), and 6 h (−0.34; 95% CI: −0.68 to −0.01), 12 h (−0.43; 95% CI: −0.71 to −0.15) and 24 h (−0.35; 95%CI: −0.59 to −0.10) after surgery, compared with the placebo patch (PP) group. Sensitivity testing suggests that opioid use could underestimate NP analgesia. Late demand for the first analgesic and consumption of rescue analgesics tended to be lower in the NP group. Conclusions: The current findings suggest, with low certainty of evidence, the analgesic potential of NP for surgical procedures. Clinical relevance: Perioperative use of NP significantly improved postoperative pain, even when opioids were administered or prescribed. Nevertheless, the clinical relevance should be interpreted with caution, owing to the effect sizes of the summary measures and methodological issues. The analgesic potential of NP as an adjuvant therapy to regulate pain and acute inflammation may offer certain clinical advantages, thus warranting further investigation.
Keywords: Meta-analysis; Nicotine patch; Opioids; Pain management; Perioperative period; Postoperative pain; Preoperative procedure